2020
DOI: 10.1002/jlb.4ma0820-655rr
|View full text |Cite
|
Sign up to set email alerts
|

SLAMF1 signaling induces Mycobacterium tuberculosis uptake leading to endolysosomal maturation in human macrophages

Abstract: Tuberculosis dates back to ancient times but it is not a problem of the past. Each year, millions of people die from tuberculosis. After inhalation of infectious droplet nuclei, Mycobacterium tuberculosis reaches the lungs where it can manipulate the immune system and survive within host macrophages, establishing a persistent infection. The signaling lymphocytic activation molecule family member 1 (SLAMF1) is a self-ligand receptor that can internalize gram-negative bacteria and regulate macrophages' phagosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…Previous work evaluating platelet count in CDI episodes reported controversial results, assigning them both a beneficial and detrimental role in relation to clinical symptoms [76][77][78][79][80][81][82][83][84][85] . We have recently shown that platelets bind to C. difficile and promote its uptake by human macrophages using macropinocytic pathways 86 . Therefore, we consider that platelets in CDI could be fundamental for the resolution of the infection and that further studies are needed to unravel their role during CDI.…”
Section: Blood and Serum Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work evaluating platelet count in CDI episodes reported controversial results, assigning them both a beneficial and detrimental role in relation to clinical symptoms [76][77][78][79][80][81][82][83][84][85] . We have recently shown that platelets bind to C. difficile and promote its uptake by human macrophages using macropinocytic pathways 86 . Therefore, we consider that platelets in CDI could be fundamental for the resolution of the infection and that further studies are needed to unravel their role during CDI.…”
Section: Blood and Serum Parametersmentioning
confidence: 99%
“…We have recently shown that platelets bind to C. difficile and promote its uptake by human macrophages using macropinocytic pathways 86 . Therefore, we consider that platelets in CDI could be fundamental for the resolution of the infection and that further studies are needed to unravel their role during CDI.…”
Section: Blood and Serum Parametersmentioning
confidence: 99%
“…0.5 x 10 6 /ml CD14 positive-selected monocytes were cultured at 37°C and 5% CO2 for 2h in absence of FBS to promote adherence. Non-adherent cells were removed and adherent cells were cultured for additional 16-18h in complete media as described before (Barbero et al, 2021) (Supplementary Figure 1A).…”
Section: Macrophagesmentioning
confidence: 99%
“…2 × 10 5 macrophages/well were cultured in chamber-slides (Nunc) as described before (Barbero et al, 2021). Cells were stimulated with CDH FITC and/or WP at the ratios indicated above in the presence or absence of endocytosis inhibitors.…”
Section: Fluorescence and Confocal Microscopymentioning
confidence: 99%